The Martini Club : The Summer Guests - Book 2 - Gerritsen, Tess (Thorndike, Maine : Center Point Large Print, 2025)
"When former spy Maggie Bird retired to the seaside hamlet of Purity, Maine, she settled in for a quiet life with breathtaking views. But enemies from her past soon threatened to destroy everything. Maggie survived, thanks to her wits and the collective intelligence of the Martini Club, the circle of ex-CIA friends in her cocktail-sipping book club. Their handiwork, however, caught the attention of young police chief Jo Thibodeau. Now Jo and her neighborhood ex-spies have an uneasy alliance. After a teenager vanishes and Maggies neighbor becomes the prime suspect she joins the investigation, determined to prove her friends innocence. But the girls wealthy family pushes for an arrest. And when authorities discover a long -dead corpse in a nearby pond, the case becomes doubly complicated, with unthinkable ties to long-buried secrets. As Jo grapples with two unexplained mysteries, the Martini Club races to uncover the truth behind shadowy secrets . . . before more lives are lost."--
Keywords: United States. -- Central Intelligence Agency -- Officials and employees; Fiction; Women spies -- Fiction; Secrecy -- Fiction; Murder -- Investigation; Fiction; Missing persons -- xInvestigation -- Fiction; Book clubs (Discussion groups) -- Fiction; Retirees -- Fiction; Maine -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Spy fiction; Large print books